Transperitoneal versus extraperitoneal approach in laparoscopic radical prostatectomy: A meta-analysis. Issue 29 (July 2018) - Wang, Kun; Zhuang, Qianfeng; Xu, Renfang; Lu, Hao; Song, Guanglai; Wang, Jianping; Tian, Zinong; Mao, Qingyan; Gong, Pengfeng
Abstract: Background: To compare the transperitoneal approach with extraperitoneal approach in laparoscopic radical prostatectomy (LRP) (including pure and robotic-assisted LRP) using meta-analytic techniques. Methods: Medline (PubMed), Embase, Ovid, CMB, and Cochrane databases were searched for studies that compared the transperitoneal and extraperitoneal approaches in LRP from January 2000 to January 2017. Outcomes included were operative time, operative bloods joss (milliliters), rate of transfusion, rate of open conversion, rate of intraoperative complications, rate of postoperative complications, and time of postoperative catheterization. Results: Thirteen studies including 1674 patients were selected for the meta-analysis. 850 (50.8%) cases had undergone transperitoneal LRP (TLRP) and 824 (49.2%) cases had undergone the extraperitoneal LRP (ELRP). Comparison of operative time between the TLRP group and the ELRP group showed no significant differences (weighted mean difference [WMD] = 21.21, 95%CI = –1.16–43.57, P  = .06). No significant differences were observed in blood loss (WMD = −6.04, 95%CI = −43.38–31.29, P  = .75) and the rate of transfusion (odds ratio [OR] = 1.03, 95%CI = 0.55–1.96, P  = .92) between the 2 groups. No significant differences were observed for the rate of intraoperative complications (OR = 1.25, 95%CI = 0.57–2.21, P  = .75) and the rate of open conversion (OR = 1.12, 95%CI = 0.32–4.97, P  = .75). Significant differences were observed in the TLRP group compared with the ELRP group (OR = 1.69, 95%CI: 1.23–2.32, P  = .001) regarding the rate of postoperative complications. Conclusions: Our meta-analysis findings revealed that the TLRP group showed no significant differences in most important indicators compared with ELRP. Moreover, TLRP showed higher rate of postoperative complications compared with ELRP.